Photoassisted photoluminescence fine-tuning of gold nanodots through free radical-mediated ligand-assembly. Issue 18 (27th April 2016) - Tseng, Yu-Ting; Cherng, Rochelle; Harroun, Scott G.; Yuan, Zhiqin; Lin, Tai-Yuan; Wu, Chien-Wei; Chang, Huan-Tsung; Huang, Chih-Ching
Abstract : UV-light irradiation can accelerate the assembly of surface thiol ligands on gold nanodots and enhances the photoluminescence quantum yield by 30-fold. Abstract : In this study, we have developed a simple photoassisted ligand assembly to fine-tune the photoluminescence (PL) of (11-mercaptoundecyl)- N, N, N -trimethylammonium bromide-capped gold nanodots (11-MUTAB–Au NDs). The 11-MUTAB–Au NDs (size: ca . 1.8 nm), obtained from the reaction of gold nanoparticles ( ca . 3 nm) and 11-MUTAB, exhibited weak, near-infrared (NIR) PL at 700 nm with a quantum yield (QY) of 0.37% upon excitation at 365 nm. The PL QY of the Au NDs increased to 11.43% after reaction with 11-mercaptoundecanoic acid (11-MUA) for 30 min under ultraviolet (UV) light, which was accompanied by a PL wavelength shift to the green region (∼520 nm). UV-light irradiation accelerates 11-MUA assembly on the 11-MUTABAu NDs (11-MUA/11-MUTAB−Au NDs) through a radical-mediated reaction. Furthermore, the PL wavelength of the 11-MUA/11-MUTAB−Au NDs can be switched to 640 nm via cysteamine under UV-light irradiation. We propose that the PL of the Au NDs with NIR and visible emissions was originally from the surface thiol–Au complexes and the Au core, respectively. These dramatically different optical properties of the Au NDs were due to variation in the surface ligands, as well as the densities and surface oxidant states of the surface Au atoms/ions. These effects can be controlled by assembling surface thiol ligands and accelerated by UV irradiation.